The Abhidharma Version of No-Self Theory - Chadha, Monima (2016)
This paper elucidates the Abhidharma attempt to revise our ordinary ways of thinking and our ordinary conceptual scheme in which the self (minimally conceived of as the referent of 'I') occupies a prime position. This revisionary metaphysics provides an intellectually and morally preferred picture of the world that lacks such a self. The no-self theory is no doubt deeply counter-intuitive. In response to this some contemporary scholars offer a weak version of the Buddhist no-self account which incorporates elements of Abhidharma and Madhyamika philosophies. I analyse two such influential attempts by contemporary philosophers who weaken the no-self account in a bid to show that we can retreive a minimal notion of self from the Buddhist account. However, to reconstruct a self from the scraps of the no-self view is to, I think, misunderstand the strategy employed by Vasubandhu. In this paper, I argue that it is a mistake to interpret the noself view as allowing for a minimal self. To be true to the spirit and arguments of the Abhidharma Buddhist philosophers we need to deny the self, period.
Keywords: Abhidharma; Abhidharma; Anatman; Buddhism; Buddhism; Metaphysics; No-self; Scholars